EFFECTIVE USE OF FAIRY TALES IN THE DEVELOPMENT OF SPOKEN AND WRITTEN LANGUAGE OF PRIMARY SCHOOL PUPILS (Konferensiyalar | Conferences, 2024)
In this article, the effective use of fairy tales in the development of oral and written speech of primary school pupils. Teaching harmonizes images with the animal world. The effect on the further expansion of the vocabulary chorus is noted. There is talk about developing the scope of world knowledge more creatively.